A critical discussion of the poetic experience in Prince Abdullah Al-Faisal’s Wahi Alhirman - Matar, Wajih Abdel Fattah Ahmad (Research Journal in Advanced Humanities, 2024)
The Saudi modern poetry has been largely influenced with the modern trends in Western and American poetry. One of the contemporary trends in Western poetry is the emphasis on the poetic experience. The traditional Saudi poetry results from a temporary occasion affecting the mood of poet producing his poem. However, the poetic experience is shaped by long-standing internal feelings and a permeate psychological state. Therefore, the present study aims to reveal the poetic experiences in the collection of poems titled “Deprivation Revelation” and “Wahi Alhirman.” The present study draws heavily on psychoanalysis and stylistic approaches to help reflect the aspects of poetic experience in the poetry of Alfaisel. The present study uses the psycho-analysis approach to interpret the poetic experience in Alfaisel's collection of poetry, The Deprivation Revelation, "Wahi Alhirman," from a psychological perspective. We then adopt a stylistic perspective to explain how the poet's internal psychological condition could significantly reshape and rebuild his poetic style, and how this condition could influence the language and meanings. The present study has yielded several significant findings, the most significant of which is that a comprehensive psychological analysis of the poet's poetic experience can yield innovative and creative understandings, as well as unprecedented interpretations of the meanings of Al-Faisel's poetry. The poetic experience enables readers to perceive the laden and invisible meanings embedded in Saudi poetry.